Briefkasten (smart mailbox) / Amirul Syahmi Shukran, Muhammad Haziq Muhammad and Muhammad Faiz Jailani - Shukran, Amirul Syahmi; Muhammad, Muhammad Haziq; Jailani, Muhammad Faiz (2019)
As we know, mails or bills are important in human life. All company and industry in this world still using mails as their communication in their business. But in our project, we are focusing on the people who live in the apartment or the high rise building. In this regard, mostly all apartments in Malaysia locate their residences mailbox at the bottom floor of the apartment. So, if the residence wants to check their bills or mails, they have to go the bottom floor to check in their mailbox. If the mails or the bill doesn't show up yet, the time and also the energy of the person have been wasted. So we design the program called BRIEFKASTEN that can solve that problem. So with this innovative program, their burden rate will decrease and will also save their time. We are targeting the average market size per month to be RM 1,329,453 in a month. While, we can achieve total market size RM 79,767,200 in a year if we approximately sell our product worth RM400 (1 unit) to 199,418 potential customer in that first year However, there are applications as competitive applications which are Ucella and Receva. Plus, these applications are have been operating for a long time before the release of Briefkasten. We estimated that the total sales will be increased 0.5 % within the three years. However, the total sales that estimated above can be changed either decreased or increased since the market sales can be affected by the others factors such as population shift, socioeconomic trends and market growth